How to learn English quickly - Sattarov Inayat Saparbayevich; Sattorova Khadicha Inayat qizi (Periodica Journal, 2023)
Understanding what elements the language consists of will help you learn English easily and quickly. Very quickly, English will start to give in as soon as you have a clear plan. It's important to focus on exactly the skills you need and get rid of some barriers
Keywords: Language; English